Agenda Setting Program Siaran Mimbar Agama Hindu TVRI NTB Dalam Mewujudkan Visi Indonesia Emas 2045 - Wijaya, I Putu Gandi Juni; Winata, I Dewa Komang Intaran Aditya; Widaswara, Rieka Yulita (IAHN Gde Pudja Mataram, 2025)
Towards the golden age of Indonesia in 2045, Indonesia's vision is to become a developed country and be on par with other superpower countries. This vision is also realized through television programs, namely Hindu religious pulpit broadcast programs located on TVRI NTB. The focus of the research is Hindu religion mimbar broadcast program materials, and their relationship to agenda setting theory. The research method is a qualitative descriptive method, where the research findings will be narrated in words. The results of the research show that Hindu religion mimbar broadcast program material that is relevant to efforts to realize the Vision of a Golden Indonesia 2045 includes, Religious Moderation from a Hindu Religious Perspective, the Relevance of Prayer Ethics in the Era of Globalization, Informal Education in Hindu Literature, Meditation to Build Humanistic Awareness, Hindu Religious Learning Media For Children with Special Needs, Sloka and Upakara Literacy from a Vedic Perspective. This is in line with the first pillar of development, namely human development and mastery of science and technology and in line with the development of science and technology, innovation, and people with religion and advanced culture. The Hindu religion mimbar broadcast program materials were obtained based on suggestions from resource persons, Hindu institutions in collaboration with TVRI NTB, and also adjusted to the overall Hindu Hindu religion mimbar broadcast program agenda map which was then selected based on the agenda setting meeting of Hindu religion mimbar broadcast program division. The Hindu religious platform as an electronic mass media program provides information to the public, especially Hindus, by prioritizing national unity and progress through the teachings of the Hindu religion.